Kinerja Masing-Masing Pusat Pertanggungjawaban dalam Organisasi Terdesentralisasi - Jessica Anastacia Dame Purba; Veri Gabriel Lumbantobing; Wendy Teguh Putri Zega; Putri Yola Lumbantoruan; Hamonangan Siallagan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Center of responsibility is essential in large complex organizations to facilitate effective supervision. They establish a hierarchical structure within the organization, where they can be autonomous units or departments. This study aims to provide an overview of performance analysis of each center of responsibility within a decentralized organization. The research employs a literature review method referring to previous studies, including journals, theses, and other relevant sources, on the performance of centers of responsibility in decentralized organizations. From the literature review, it is found that periodic reports prepared by centers of responsibility are timely, but some aspects of the reports do not align with theoretical studies. The performance of centers of responsibility is still insufficiently evaluated due to the lack of informative reporting. There are four types of centers of responsibility: Cost Centers, Revenue Centers, Profit Centers, and Investment Centers, which design a framework to directly link performance measurement with organizational goals across various strategic areas. Perforevaluation in most decentralized organizations predominantly focuses on achieving profit and turnover, necessitating clearer criteria to ensure branch managers effectively manage their respective branches.